FEATURES OF SURGICAL TREATMENT OF BRAIN CANCER WITH PRIMARILY MULTIPLE POLYNEOPLASIAS - Alikhodjaeva , G.A.; Altibaev , U.U.; Tashmatov , Sh.N. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2022)
The term «multiple malignant polyneoplasia» implies the absence of anatomic connections between histologically confirmed independent malignant tumors, where the subsequent tumor is not a continued growth or metastasis of the primary tumor. An increase in the contingent of long-term patients with oncological diseases increases the overall cumulative probability of a second tumor. The presence of multiple neoplastic lesions leads to a synergistic negative effect of each of the tumors on the patient’s body and a reduction in the patient’s chances to undergo treatment.